Relationship between sources of counseling self-efficacy and counseling self-efficacy among Malaysian school counselors - Ooi, Pei Boon; Wan Jaafar, Wan Marzuki; Baba, Maznah (Elsevier, 2018)
School counselors’ role in the formation and transformation of the Malaysian education system is indispensable. This study employs the Social Cognitive Theory to examine the relationship between the sources of counseling self-efficacy and the Malaysian school counselors’ counseling self-efficacy. The Sources of Counseling Self-Efficacy questionnaire and the Counseling Self-Estimate Inventory were used on 541 school counselors nationwide, as the respondents. The result reveals mastery experience has the strongest relationship with counseling self-efficacy. Recommendations on how to strengthen self-efficacy are proposed.